Proteins derived from green biomass: Alfalfa (Medicago sativa L.) and water lentil concentrate (Lemna minor L.) in the focus as stabilizers for emulsions - Maren Müller; Olaf Holderer; Kuno Schwärzer; Anika Wiese-Klinkenberg; Beate Förster; Stephan Förster; Joachim Kohlbrecher; Kathleen Wood; Baohu Wu; Stephan Hauschild; Henrich Frielinghaus; Theresia Heiden-Hecht (Food Hydrocolloids for Health)
Green crop biomass is a sustainable protein source, which can support solving global food challenges as well as improving the bioeconomy for novel food utilization. Two green biomasses -alfalfa and water lentil- known for a high protein content and their value as feed and food components were investigated for their potential in stabilizing emulsions.For interfaces in complex food systems like emulsions, the proteins from the green biomasses act similarly to other plant proteins and even to some extent to whey proteins. The extracted green biomass protein concentrates were composed of a diverse mixture of proteins: RuBisCo as the main component, enzymes like ATP subunit synthase, chlorophyll a-b binding proteins, histones and cytochromes, which all were associated as protein aggregates or protein-polyphenol complexes with sizes from 33 up to 85 nm.These multicomponent and complex green protein components were obtained in an extraction process, and proved their capability to stabilize emulsions. Key parameters are a narrow oil droplet size distribution with rather small oil droplets with a median of about 3.5 μm, a low interfacial tension with around 15 mN/m and an elastic interfacial layer with an elastic modulus of about 45 mN/m comparable to functional whey or plant proteins. The oil/water interface of the emulsion revealed a more pronounced structural rearrangement for alfalfa protein compared to water lentil proteins as quantified by small-angle neutron scattering (SANS), indicating the relevance of plant protein source to the final structure.Green biomass proteins from alfalfa and water lentil represent a novel protein source to stabilize emulsions.